Effectiveness of different serve types and their influence on reception quality and first attack performance of the opponent (based on Women’s Superleague teams) - Smirnov, A.A. (Theory and Practice of Physical Culture, 2026)
The relevance of the study stems from the evolving role of the serve in elite women’s volleyball: once a mere means of putting the ball into play, it has become a tool for controlling the opponent’s attacking patterns, yet the conventional “ace versus error” metric fails to capture this tactical effect. Objective of the study is to quantify the influence of the opposing team’s serve-type composition on reception quality, attacking action characteristics, and rally outcome in Russian Women’s Superleague clubs. Methods and structure of the study. Methods comprised pedagogical observation and video analysis of 1,436 rallies involving 22 athletes from VC Dynamo Moscow and VC Minchanka; Pearson’s χ² test, Cramer’s V, odds ratios (OR), and Student’s t-test were employed. Results and conclusions. Results indicate that a variable serve composition yields a significantly higher proportion of disrupted opponent receptions, greater suppression of quick attacks, and a higher serve-rally win rate, despite no significant difference in the aggregate serve efficiency index.